2022
DOI: 10.1155/2022/4598725
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnosis Framework for High‐reliability Equipment with Small Sample Based on Transfer Learning

Abstract: Conventional methods for fault diagnosis typically require a substantial amount of training data. However, for equipment with high reliability, it is arduous to form a large-scale well-annotated dataset due to the expense of data acquisition and costly annotation. Besides, the generated data have a large number of redundant features which degraded the performance of models. To overcome this, we proposed a feature transfer scenario that transfers knowledge from similar fields to enhance the accuracy of fault di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Aiming at the accuracy of wind speed prediction models, Yousuf et al established four machine learning models to analyze small sample data, which effectively improved the overall prediction accuracy [19]. In order to improve the accuracy of diagnosis with small sample, Pan J et al proposed a CNN weighted training model to solve the redundancy problem of large amount of data [20]. The proposed method can improve the fault diagnosis rate by 28.6%.…”
Section: Literature Reviews and Objectivesmentioning
confidence: 99%
“…Aiming at the accuracy of wind speed prediction models, Yousuf et al established four machine learning models to analyze small sample data, which effectively improved the overall prediction accuracy [19]. In order to improve the accuracy of diagnosis with small sample, Pan J et al proposed a CNN weighted training model to solve the redundancy problem of large amount of data [20]. The proposed method can improve the fault diagnosis rate by 28.6%.…”
Section: Literature Reviews and Objectivesmentioning
confidence: 99%
“…Alzubaidi et al 29 proposed a novel transfer learning approach to fill the performance gap of deep learning models when there was a lack of training data in medical imaging tasks. Jing et al 30 suggested a feature transfer framework that depends on transferring knowledge from related fields to facilitate and reduce the challenges of fault diagnosis with small samples.…”
Section: Literature Reviewmentioning
confidence: 99%